A characterization of edge-perfect graphs and the complexity of recognizing some combinatorial optimization games - Dobson, Maria Patricia (2013)
We characterize edge-perfect graphs and prove that it is co-NP-complete to recognize them. In consequence, recognizing the defining matrices of totally balanced packing games is also co-NP-complete, in contrast with the polynomiality for the covering case. In addition, we solve the computational complexity of universally balanced (with respect to the resources constraints) packing games.